Preventing Foodborne Illness: E. coli O157:H7 - Keith R. Schneider; Renée Goodrich Schneider; Ploy Kurdmongkoltham; Bruna Bertoldi (EDIS)
This seven-page fact sheet discusses the common foodborne pathogen E. coli O157:H7, especially as it concerns food handlers, processors and retailers. Written by Keith R. Schneider, Renée Goodrich Schneider, Ploy Kurdmongkoltham, and Bruna Bertoldi and published by the Food Science and Human Nutrition Department.http://edis.ifas.ufl.edu/fs097